Amid Social Contradictions : Towards a History of Social Work in Europe. - Hauss, Gisela (Barbara Budrich-Esser, 2009)
How does social work keep its balance between the requirements of its clients and its role as agency of state and society? In the historical analyses from various countries international experts show, how social work has succeeded in keeping those conflicting demands at bay. The contributions look at the historical situations in Finland, Germany, Hungary, the Netherlands, Poland, the Republic of Ireland, Russia, the former Soviet Union, Switzerland, and former Yugoslavia.